ANALYSIS OF THE ROLE OF COMMUNITY BUSINESS AND SOCIAL CAPITAL IN THE DEVELOPMENT OF COMMUNITY-BASED TOURISM - Gesta Lionanda; Kurniawati Kurniawati (Journal of Social Research, 2024)
Community-Based Tourism is stated as the development of tourism managed and supervised by the community so that the community has a big role in its development, but the implementation of community-based tourism to achieve sustainable tourism also has negative impacts in the form of cultural degradation, inequality of benefits, economic inequality, lack of participation and capacity of local communities. Contrary to these problems, this study aims to analyze the role of community entrepreneurship in the development of Community-Based Tourism. Primary data collection techniques through in-depth interviews while secondary data collection techniques through literature studies. The results showed that BUMDes as Community Entrepreneurship in the Village play a role as tourism business managers, tourism infrastructure development, the main driver of promotion and marketing, local product development, running partnerships with external parties, and carrying out environmental conservation. Then Social Capital plays a role in increasing community support and participation, increasing trust between communities, tourists and institutions that manage tourism, equality and social inclusion, and minimizing conflicts in society. Efforts have been made in the development of community-based tourism to achieve sustainable tourism through the provision of training and education, conservation of the environment, culture and traditions, development of sustainable local products and services, and empowerment of local communities. The challenge faced is the need to optimize the capacity and quality of human resources from managers and communities who act as business actors so as to optimize collaboration with the pentahelix approach and increase community confidence. Concretely, this tourism development contributes to SDGs 1, 2, 3, 4, 5, 6, 8, 10, 12, and 17